PENGEMBANGAN BAHAN AJAR MODUL BERBASIS PHOTOSHOP PADA MATA PELAJARAN BACA TULIS QUR’AN - Ndun Saedul Hoer; Elly Sukmanasa; Fitri Anjaswuri (STKIP Subang, 2022)
This study aims to develop photoshop-based module teaching materials in the subjects of reading and writing the Qur'an with third grade students of the Green Bhakti Insani Integrated Islamic Elementary School. This type of research is Research and Development. The research procedure stage uses the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation with a limited deployment stage in class III consisting of 31 students. Research data were collected through interviews, distribution of respondent questionnaires, and documentation. The research instrument was in the form of expert validation sheets and teacher and student response questionnaires. Assessment of expert validation results obtained value; material expert validation (84%), linguist validation (68%), and media expert validation (84%) with an average of 78% having proper criteria. While the student response questionnaire obtained a score of 88.7% has very decent criteria. Based on the results of research on the feasibility of module teaching materials, it can be concluded that photohsop-based module teaching materials are very feasible to be used in the learning process in the Qur'anic reading and writing subjects and can foster students' enthusiasm for learning.